Case report-patient with cerebellar stroke and percutaneous enterogastric tube - Arsovska, Anita; Stojchev, Sasho; Kolevski Goran; GJorcheva, Irena; Babunovska Marija; Mitrevska Velkov Jasmina; Isjanovski, Igor; Grivcheva Stardelova, Kalina; Deriban, Gjorgji (My University, 2017)
Abstract Introduction: Cerebellar strokes occur in 1,5-2,3% of all ischemic stroke cases. Aim: We present 74-year-old male patient, admitted at the University Clinic of neurology due to acute ischemic cerebellar stroke with speech and swallowing difficulties, disturbed balance, weakness of the left side extremities, impaired consciousness. Case report: On admission the patient was presented with clinical picture of left hemicerbellar syndrome with compression of the medulla. Computer tomography of the brain (CT)on admission was with normal finding. Control CT of the brain after 48 hours showed irregular ischemic lesion in the left cerebellar hemisphere. Nuclear magnetic resonance imaging (MRI) of the brain confirmed the CT findings. Color duplex sonography of the vertebral arteries (VA)showed reduced Doppler signal in the left VA,finding conclusive with distal occlusion and compensatory increased blood flow velocity in the right VA. CT angiography of vertebral arteries showed hypoplastic extracranial segment of the left VA, while its intracranial segment could not be visualized. Posterior inferior cerebellar artery (PICA) was not visualized intracranially as well, finding conclusive with its occlusion. The right VA on CT angiography was seen with compensatory increased lumen. Patient was treated with usual therapy for ischemic stroke during a period of 3 weeks. Due to dysphagia, nasogastric feeding tube was placed. During the stay in hospital, the patient's physical and neurologicl status gadually improved, But, dysphagia still persisted and according to current guidelines for stroke treatment, together with the specialists from the Clinic of Gastroenterohepatology, we decided to place a percutaneous enterogastric tube (PEG). The intervention went very well and the patient was discharged for home treatment. He came for regular control check-ups every month for a period of 1 year. His physical and neurological symptoms gradually improved, and his swallowing function recovered. After 6 months, the PEG probe was taken out, and the patient continued to eat and swallow normally. Discussion: Dysphagia is a serious complication after stroke. It carries risk for aspiration and occurrence of pneumonia. Placement of nasogastric feeding tube is recommended in patients who have swallowing difficulties in the acute phase of stroke. Placement of PEG tube is recommended 2 weeks after stroke occurrence. Studies so far have shown that feeding through the PEG tube is more efficient than feeding through the nasogastric tube in terms of improved nutritive status and has lower complication risk. Conclusion: Successful treatment of stroke depends on many factors. Particular attention should be brought to the food and beverage intake, and assessment of early signs and risk factors of dysphagia in order to take appropriate therapeutic measures.
Keywords: cerebellar stroke, percutaneousenterogastric tube